Serial blood lactate levels as a prognostic factor for sepsis mortality - Keswari Aji Patriawati; Nurnaningsih Nurnaningsih; Purnomo Suryantoro (Indonesian Pediatric Society, 2014)
Background Sepsis is a major health problem in children and aleading cause of death. In recent decades, lactate has been studiedas a biomarker for sepsis, and as an indicator of global tissuehypoxia, increased glycolysis, endotoxin effect, and anaerobicmetabolism. Many studies h ave shown both high levels andincreased serial blood lactate level measurements to be associatedwith increased risk of sepsis mortality.Objective To evaluate serial blood lactate levels as a prognosticfactor for sepsis mortality.Methods We performed an observational, prospective study in thePediatric Intensive Care Unit (PICU) at DR. Sardjito Hospital,Yogyakarta from July to November 2012. We collected serialblood lactate specimens of children with sepsis, first at the time ofadmission, followed by 6 and 24 hours later. The outcome measurewas mortality at the end ofintensive care. Relative risks and 95%confidence intervals of the factors associated with mortality werecalculated using univariate and multivariate analyses.Results Sepsis was found in 91 (50.3%) patients admitted tothe PIW , of whom 75 were included in this study. Five patients(6. 7%) died before the 24-hour lactate collection and 39 patients(52.0%) died during the study. Blood lactate levels of 4mmol;Lat the first and 24-hour specimens were associated with mortality(RR 2.9; 95%CI 1.09 to 7 .66 and RR 4.92; 95%CI 1.77 to 13.65,respectively). Lactate clearance of less than 10% at 24 hours(adjusted RR 5.3; 95% CI 1.1 to 24.5) had a significantly greaterrisk fo llowed by septic shock (adjusted RR 1.54; 95%CI 1.36 to6.4 7) due to mortality.Conclusion In children with sepsis there is a greater risk of mortalityin those with increasing or persistently high serial blood lactatelevels, as shown by less than 10% lactate clearance at 24-hours afterPIW admission.